Village Financial Management StrategyLombok Timur District (Case Study In Keruak District) - Syaefullah; Marzuki (International Journal of Scientific Research, 2024)
One of the positive impacts of regional autonomy is the change in the government system from a centralized system to a decentralized system. Decentralization in regional autonomy means that there is a delegation of authority from the central government to regional governments. The delegation of authority means the granting of authority and flexibility to the regions to manage and utilize regional resources optimally. Although the emphasis on autonomy is placed at the Regency/City level, in essence, independence must start from the lowest level of government, namely the Village. Because government starts from the village, as a follow-up to the provisions contained in Law Number 23 of 2014 concerning Regional Government, Law Number 6 of 2014 concerning Villages was issued. Article 1 of Law Number 6 of 214 concerning Villages states that: "The village is a legal community unit that has territorial boundaries that are authorized to regulate and manage government affairs, the interests of the local community based on community initiatives, origin rights, and/or rights. recognized and respected in the system of government of the Unitary State of the Republic of Indonesia. The research objectives are: To analyze the Village Financial Management strategy in 2 villages namely Stungkep Lingsar Village and Mendana Raya Village, Keruak District, East Lombok Regency, for the 2015-2018 fiscal year. The research method used is a qualitative research method, while the results of the research are as follows: There is a very clear difference between financial management in Setungkep Lingsar Village and financial management in Mendana Raya Village. Village financial management in Setungkep Lingsar Village, starting from the planning, implementation, administration, reporting and accountability processes have been going well and correctly in accordance with applicable regulations, while village financial management in Mendana Raya Village, in terms of activities related to Planning, Management Business, Reporting and Accountability have been carried out properly and correctly in accordance with applicable regulations, especially the provisions in Permendagri Number 113 of 2014 concerning Village Financial Management, only in terms of carrying out activities that deviate from existing provisions, where the transfer of funds to build and or finance other activities that are considered urgent and have not been listed in the APBDesa, not accompanied by changes in the APBDesa. Suggestion, the East Lombok Regency Government and the Village Head and related agencies to provide in-depth understanding to village government officials either through education education and training as well as through courses related to village financial management